Influence of pulse electromagnetic radiation on performance of electric radio products - Serkov, A. A.; Breslavets, V. S.; Breslavets, Juliya; Yakovenko, I. V.; Yatsenko, I. L. (Національний університет "Полтавська політехніка імені Юрія Кондратюка", 2024)
The subject matter is the processes of analysis of the occurrence of reversible and irreversible failures of semiconductor devices under conditions of exposure to electromagnetic radiation. It is shown that the influence of pulsed electromagnetic radiation is accompanied by the emergence of currents in the conductive elements of products and the emergence of their internal fields. The mechanisms for the occurrence of instabilities of natural oscillations of semiconductor components of electrical and radio products, caused by their interaction with flows of charged particles, have been determined. The presence of instabilities of this kind has a significant impact on the spectral (operating) characteristics of electrical radio products. The results obtained in the work make it possible to assess the degree of influence of pulsed electromagnetic radiation on the operating (volt-ampere) characteristics of electrical radio products. The aim is a model of the mechanisms of the emergence and development of instabilities of natural oscillations of semiconductor structures, components of electrical radio products (communication equipment), in the presence of currents and voltages induced by pulsed electromagnetic radiation. The implementation of such a model is due to the possibility of transforming the energy of a flow of charged particles induced by external electromagnetic radiation into the energy of natural vibrations of a semiconductor structure, taking into account the properties of the structure itself (size, concentration of free carriers, permeability). The transformation of the energy of currents induced by electromagnetic radiation into natural vibrations of a semiconductor structure is determined by two effects (transition or Cherenkov radiation) depending on the location of the structure relative to the direction of the currents. The objectives are: the main electromagnetic effects affecting performance of electrical radio products (ERI) under exposure conditions external pulsed radiation and also indicates characteristic changes ERI parameters that determine their functional purpose, which are a consequence of these effects. The methods used are the method of successive approximations over a small parameter, which allows one to determine the spectrum of natural oscillations of a semiconductor device and the mode of their amplification (instability). The following results are obtained. The results of studies characterizing the malfunction of electrical radio products under conditions of exposure to third-party electromagnetic radiation are presented, as well as the main parameters characterizing the electromagnetic resistance of electronic devices to the effects of pulsed currents and voltages. The characteristic types of malfunctions of semiconductor devices (SCD), components of electronic components, in areas of irreversible and reversible failures, as well as the levels of intensities and currents of electric and magnetic fields affecting the SPD, separating the areas of reversible and irreversible failures, are given. Using the energy approach, a physical model of the occurrence of one of the types of reversible failures of the semiconductor element base (the appearance of S-shaped sections of current voltage characteristics) has been developed. This physical model makes it possible to determine the criteria for the electromagnetic resistance of a number of semiconductor devices to the effects of external pulsed radiation and also to obtain calculated ratios for assessing the degree of deviation of the operating characteristics of the PPP from the norm. Conclusion. Development of design relationships that determine the modes of amplification (generation) of oscillations of electrical radio products, making it possible to determine the degree of distortion of their current-voltage characteristics (reversible failures) and complete loss of performance (irreversible failures) depending on the parameters of external electromagnetic radiation. The results obtained in the work can be used in the development of amplifiers, generators and frequency converters operating in the millimeter and submillimeter range that are resistant to external electromagnetic radiation. Quantitative estimates of the criterion for reversible failures (instability increments) show that the amount of radiation energy lies within the sensitivity of modern submillimeter radiation receivers and is the cause of failures.

Предметом досліджень є процес аналізу появи оборотних та незворотних відмов напівпровідникових приладів за умов впливу електромагнітного випромінювання. Показано, що вплив імпульсного електромагнітного випромінювання супроводжується виникненням струмів у провідних елементах виробів та виникненням внутрішніх полів. Визначено механізми виникнення нестійкостей власних коливань апівпровідникових комплектуючих електрорадіовиробів, які зумовлені їхньою взаємодією з потоками заряджених частинок. Наявність нестійкостей такого роду істотно впливає на спектральні (робочі) характеристики електрорадіовиробів. Отримані в роботі результати дозволяють оцінити ступінь впливу імпульсного електромагнітного випромінювання на робочі (вольт-амперні) характеристики електрорадіовиробу. Метою статті є розробка моделі механізмів виникнення та розвитку нестійкостей власних коливань напівпровідникових структур, що комплектують електрорадіовироби (апаратуру зв'язку), за наявності струмів та напруг, наведених імпульсним електромагнітним випромінюванням. Реалізація подібної моделі обумовлена можливістю трансформації енергії потоку заряджених частинок, наведеного зовнішнім електромагнітним випромінюванням, в енергію власних коливань напівпровідникової структури з урахуванням властивостей самої структури (розмірами, концентрацією вільних носіїв, проникністю). Трансформація енергії наведених електромагнітним випромінюванням струмів у власні коливання напівпровідникової структури визначається двома ефектами (перехідного чи черенківського випромінювань) залежно від розташування структури щодо напрями струмів.
Вплив імпульсного електромагнітного випромінювання на працездатність електрорадіовиробів
Keywords: semiconductor components; induced current; electromagnetic radiation; instability of oscillations; surface vibrations; напівпровідникові комплектуючі; наведений струм; електромагнітне випромінювання; нестійкість коливань; поверхневі коливання